1982
DOI: 10.1148/radiology.143.2.7071337
|View full text |Cite
|
Sign up to set email alerts
|

Injury to the intima of the hepatic artery. Results of follow-up in 11 cases.

Abstract: Injury to the intima of the hepatic artery is an uncommon complication of selective arteriography. Eleven such cases were followed up for less than or equal to 12 months. The status of the vessels, the experience of the angiographer, and the materials used for catheterization all affected the frequency of injury, which was manifested by a spectrum of changes including an intimal flap, aneurysm, dissection, and occlusion. No patient had significant changes in liver function. Progression to complete arterial occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Few studies have investigated TACE procedures using 8 microcatheters. In the present series, the incidence of arterial injury during TACE was 1.7%, which is relatively low and similar to the results of previous reports [5,6,9,10]. In addition, 34 cases of arterial injury were caused by 0.016-inch guide wire.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Few studies have investigated TACE procedures using 8 microcatheters. In the present series, the incidence of arterial injury during TACE was 1.7%, which is relatively low and similar to the results of previous reports [5,6,9,10]. In addition, 34 cases of arterial injury were caused by 0.016-inch guide wire.…”
Section: Discussionsupporting
confidence: 90%
“…The recanalization rate in the present study (91.7%) was higher than that reported in previous studies. Previous studies have reported recanalization rates of 71% and 64% in the celiac or hepatic artery after intimal injury [5,6,9].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation